2022
DOI: 10.1021/acs.jafc.2c03861
|View full text |Cite
|
Sign up to set email alerts
|

5-Methyltetrahydrofolate Is a Crucial Factor in Determining the Bioaccessibility of Folate in Bread

Abstract: This study investigated the bioaccessibility of folate in wheat bread baked with different ingredients and processing methods. Next, different matrices were spiked with 5-methyltetrahydrofolate, gallic acid (GA), or both to investigate the stability of 5-methyltetrahydrofolate during in vitro digestion. The folate bioaccessibility in bread varied from 44 to 96%. The inclusion of whole-grain or faba bean flour significantly improved both folate content and bioaccessibility. Baking with yeast increased the folat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 54 publications
(100 reference statements)
1
10
0
Order By: Relevance
“…Theoretically, processing could have affected the extractability of folate if the compounds were bound to the structures formed in the extrusion process. However, Liu et al [ 31 ] previously determined good recovery of folate in faba bean flour analysed with the same method as used in this study. Overall, the retention of folate in extrudates and its liberation should be studied in the future.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Theoretically, processing could have affected the extractability of folate if the compounds were bound to the structures formed in the extrusion process. However, Liu et al [ 31 ] previously determined good recovery of folate in faba bean flour analysed with the same method as used in this study. Overall, the retention of folate in extrudates and its liberation should be studied in the future.…”
Section: Resultsmentioning
confidence: 83%
“…Folate vitamers were extracted using a tri-enzyme treatment with α-amylase, hog kidney conjugase, and protease as previously described by Edelmann et al [ 30 ]. Total folate content was determined as a sum of the vitamers—H 4 folate, 5-CH 3 -H 4 folate, 5-HCO-H 4 folate, PGA, 10-HCO-PGA, and 5,10-CH + -H 4 folate—using the UHPLC method validated by Liu et al [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is the only method that can measure different folate vitamers simultaneously, which is important for understanding the stability of folate during digestion. With the advancement of modern chromatography technology, the time for chromatographic analysis has been reduced significantly over the past two decades (Kariluoto et al., 2001; Liu et al., 2022b). Additionally, the accuracy and sensitivity of the measurement have been significantly improved with the application of mass spectroscopic technology with isotopically labeled internal standards (Ložnjak et al., 2020).…”
Section: Folate Content and Analysis In Foodsmentioning
confidence: 99%
“…Liu et al. (2022b) investigated folate bioaccessibility in various wheat breads and found that the stability of 5‐methyltetrahydrofolate was better in faba bean wheat bread than in other types of wheat bread. Faba bean wheat bread also had the highest free phenolic content.…”
Section: Factors In Foods Affecting Folate Bioaccessibilitymentioning
confidence: 99%
“…Folate is the generic term for a family of compounds, as a water-soluble B-vitamin, including folic acid, 5-methyltetrahydrofolate (5-MTHF), 5-formyltetrahydrofolate (5-FTHF), etc. 1 5-MTHF is a vital substance for cell proliferation and tissue growth, which playing a crucial role in one-carbon transfer reactions in biosynthetic and epigenetic processes, it is the predominant physiologic form of folate found in blood and umbilical cord blood. 2 The deficiency of folate may lead to defects in the development of the neural system of the fetus.…”
Section: Introductionmentioning
confidence: 99%